America : - Tindall, George Brown (W. W. Norton, 1992)
A chronological history of American history which has been revised to emphasize immigration and its impact on the evolution of American society and culture. Biographical details of major political figures have been included, as well as a chapter on the Reagan and Bush presidencies.